Identification of paprika (Capsicum annuum L) genotype(s) for yield and quality characters - Lekshmi S L (Department of Olericulture, College of Agriculture, 2012)
The experiment entitled “Identification of paprika (Capsicum annuum L.) genotype(s) for yield and quality characters” was conducted at the Department of Olericultue, College of Agriculture, Vellayani, during the period 2011-2012. The study envisaged assessment of genetic variability in paprika and to study the influence of harvest maturity on quality parameters. Fifty three accessions of paprika were collected from different parts of country and grown in the field in RBD with three replications. The analysis of variance revealed highly significant differences among the 53 accessions of paprika for all the characters studied viz., plant height, primary branches, days to flowering, days to maturity, node to first flower, height of node to first flower, fruit length, fruit girth, fruit weight, fruits per plant, yield per plant, pedicel length, fruit: pedicel ratio, flesh thickness, seeds per fruit, flesh: seed ratio, driage, oleoresin, colour, ascorbic acid, capsaicin, bacterial wilt and leaf curl virus incidence. Among the accessions CA 6 recorded highest yield per plant (776.12 g) and CA 12 recorded maximum number of fruits (265.33). Fruit weight was highest in CA 47 (13.43 g). High phenotypic coefficient of variation and genotypic coefficient of variation were observed for yield per plant, fruits per plant, fruit weight and primary branches per plant. High heritability and high genetic advance also observed for these characters. The path analysis revealed that fruit weight, fruits per plant, plant height and primary branches had direct effect on yield per plant. Correlation and path analysis revealed that fruits per plant is the primary component as evident from the positive correlation as well as high direct and indirect effect on yield. Maximum oleoresin content was observed in CA 7 followed by CA 29 and CA 37. CA 2 recorded a high color value with pungency and CA 37 recorded a high colour with low pungency. CA 38 recorded maximum ascorbic acid content. CA 34 and CA 40 had the minimum pungency and CA 10 recorded the maximum pungency. Bacterial wilt and leaf curl virus incidence among the 53 accessions were studied. CA 33, CA 34, CA 35 and CA 47 recorded less incidence of both diseases. Based on Mahalanobis D2 analysis the current genotypes were grouped into four clusters. Cluster I was the largest with 34 accessions, followed by cluster IV with 15 accessions and cluster II with three accessions. Cluster III had only one accession. In the present study maximum divergence was observed between clusters II and IV as shown by their high intercluster distance. The minimum intercluster distance observed between the clusters I and II indicated a close relationship among the accessions. Based on selection index including both quantitative and qualitative characters CA 34 (Local, Dharwad) was ranked first followed by CA 7, CA 6, CA 33 and CA 35. The accessions were genetically catalogued and the result revealed distinct variations among the accessions for vegetative, inflorescence, fruit, seed and quality characters. Quality characters showed significant differences among the accessions and harvest maturity stages. Oleoresin, colour and capsaicin content in the paprika fruits were found to increase as the age of the fruits increased. Ascorbic acid content in the fruits increased from turning stage to red ripe and then declined. On the basis of the present study the high yielding accessions can be grouped into low pungent and pungent paprika. Among the low pungent, high yielding accessions CA 34, CA 33 and CA 35 recorded high colour value also. CA 6 and CA 7 are promising high yielding pungent paprika accessions. These accessions can be utilized for further crop improvement programmes.